Mating behavior of the tomato leafminer Scrobipalpula absoluta (Lepidoptera: Gelechiidae) - Hickel, Eduardo Rodrigues; Vilela, Evaldo Ferreira; Lima, José Oscar Gomes de; Della Lucia, Terezinha Maria Castro (Pesquisa Agropecuaria Brasileira, 1991)
Mating behavior of the tomato leafminer, Scrobipalpula absoluta, Meyrick 1917, Lepidoptera: Gelechiidae), was observed in plastic box and wind tunnel experiments. The sequence of mating behavior can be divided into two phases: long-range female location and short-range courtship. Long-range location includes those components of the search behavior (quiescence, quiescence with antenal V, flying, and walking while wing fanning) that lead to the arrival of the males in the vicinity of females. Close-range courtship includes those components of the copulatory behavior (contact with female, copulation attempt and copulation) that coordinate the interaction of both sexes. The process of searching by walking while wing fanning was essential for effective finding of female and was characterized by rapid and frequent turning near pheromone source. Sex pheromone extracts made from excised ovipositors elicited responses indistinguishable from those to calling females and can be used in sticky traps as pheromone source.